2020
DOI: 10.3389/fpsyg.2020.00941
|View full text |Cite
|
Sign up to set email alerts
|

Regular Open-Skill Exercise Generally Enhances Attentional Resources Related to Perceptual Processing in Young Males

Abstract: This study aimed to examine whether the regular open-skill exercise led to a selective improvement or a general improvement on cognitive function in healthy young males. Besides, we also intend to expand previous studies by looking into the temporal dynamics of early information processes and cognitive processes through appraising the extensive temporal series of stimulus-locked ERP components. Sixty healthy young males were classified into two groups: those who regularly participated in the open-skill exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…The fact that OSG presented better performance than SG in the incongruent, rather than congruent condition, was almost expected. Given their unpredictable nature, the open skill sports require a high level of inhibitory control compared with closed-skill sports reflecting the incongruent conditions with distractors 25 . With regards to CSG, our data revealed no inhibitory control advantage on closed skill sport participants, who had similar response time and accuracy to sedentary group, despite higher level of physical activity (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that OSG presented better performance than SG in the incongruent, rather than congruent condition, was almost expected. Given their unpredictable nature, the open skill sports require a high level of inhibitory control compared with closed-skill sports reflecting the incongruent conditions with distractors 25 . With regards to CSG, our data revealed no inhibitory control advantage on closed skill sport participants, who had similar response time and accuracy to sedentary group, despite higher level of physical activity (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several findings assume that—apart from exercise intensity—the modality of the exercise performed may modulate the beneficial response of the brain to exercise (Voelcker-Rehage et al 2010 ; Tsai et al 2017 ). Cross sectional studies suggest that challenging coordinative exercise, where the individuals are asked to actively engage within the environment, seems to induce a more beneficial effect on cognitive functions in terms of inhibitory control (Wang et al 2013a ), temporal processing (Wang et al 2013b ), task switching (Yu et al 2017 ) or perceptual processing (Zhou et al 2020 ) compared to exercise with restricted coordinative demands or cardiovascular exercise only. A potential stimulus for these superior adaptations are the highly cognitive and multisensory demands of coordinative exercise (Wang et al 2013a ).…”
Section: Introductionmentioning
confidence: 99%
“…The requirements of coordination exercise may change when performed in an unpredictable environment referred to as open-skill exercise (Schmidt and Wrisberg 2004 ). Sports like, badminton, table tennis (TT), tennis and team sports are characterized by everchanging stimuli requiring subsequent adaptation of movement to the dynamic environment (Gu et al 2019 ; Ingold et al 2020 ; Zhou et al 2020 ). For instance, during TT it is essential to track the movement of the ball, anticipate the trajectory, react correspondingly and finally return towards the opponent’s court (Akpinar et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study showed that regular open-skill exercise promotes executive functions, likely due to various sport training characteristics that involve more complex cognitive processes [ 12 ]. Similarly, open-skill exercise had been demonstrated to improve executive network efficiency compared to closed-skill exercise [ 13 ].…”
Section: Introductionmentioning
confidence: 99%